A Study of Preferences of Consumer Packs for Toffees/candies - Harnath, G.; Subrahmanyam, S. E. V. (Indian Journal of Marketing, 2005)
Most Physical products have to be packaged and labeled. Many marketers have called packaging a fifth P, along with price, products, place and promotion. Most marketers treat packaging as an element of product strategy. Packaging includes the activities of designing and producing the container for a product. Packaging has become a potent marketing tool. Well-designed package can create convenience and promotional value. Various factors have contributed to growing use of packaging as a marketing tool.